Mechanical evaluation for laminated bamboo lumber along two eccentric compression directions - Li, Hai-tao; Wu, Gang; Zhang, Qi-sheng; Su, Jing-Wen (Journal of wood science, 2016)
To evaluate the mechanical performance under two eccentric compression directions, 80 laminated bamboo lumber (LBL) column specimens were tested and analysed. Mechanical properties along two directions were compared. Bamboo nodes and drill hole are two main failure reasons for the specimens under two eccentric directions. More crack layers appeared for radial eccentric direction group specimens due to the layer structure. No matter which eccentric directions they are, the lateral deflection curves are close to the sine line, and the strain across the cross section of the LBL column for each specimen is basically linear throughout the loading process, following standard normal section bending theory. The mechanical properties for two directions are similar with each other and could follow the same design rules. Although the mechanical properties are similar for both LBL columns and parallel bamboo strand lumber (PBSL) columns as a whole, there are still some clear performance differences between the two kinds of materials. Combined all the test data under two eccentric directions, an equation for calculating the radial eccentricity influencing coefficient φ e of LBL columns is proposed. The calculation results obtained from the equations give a good agreement with the test results.